2017
DOI: 10.18011/bioeng2017v11n2p154-163
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum Brasilense via Foliar E Doses De Nitrogênio Em Cobertura Na Cultura Do Trigo Na Região De Itapeva-Sp

Abstract: RESUMOA utilização de bactérias diazotróficas na agricultura, especialmente em gramíneas, tem por finalidade incrementar a produção e produtividade aliando com menor dose ou supressão das fontes nitrogenadas aplicadas para fertilização do solo. Diante disso, o trabalho objetivou avaliar a viabilidade da inoculação de Azospirillum brasilense via foliar com doses de nitrogênio em cobertura na produção e produtividade do trigo. O experimento foi implantado na Fazenda Bom Viver, Bairro dos Prestes em Itapeva-SP, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Relative to the lower stratum, there was a linear increase in forage mass, leaf biomass and stem mass with increasing N rates (Figure 3) in the first and third cuttings, with no effect of inoculation. These results are related to an increase of stem size, the number of leaves and tillers when nitrogen is highly available in the soil for wheat (Ferreira et al, 2017).…”
Section: Resultsmentioning
confidence: 92%
“…Relative to the lower stratum, there was a linear increase in forage mass, leaf biomass and stem mass with increasing N rates (Figure 3) in the first and third cuttings, with no effect of inoculation. These results are related to an increase of stem size, the number of leaves and tillers when nitrogen is highly available in the soil for wheat (Ferreira et al, 2017).…”
Section: Resultsmentioning
confidence: 92%
“…However, differently from these authors as well as to Fukami et al (2016), in the present work any yield promotion can be attributed to tillering, as NTP data was not significant (Table 2). Nunes et al (2015) and Ferreira et al (2017) also did not reported any increase of NTP as result of inoculation and attributed the crop lack of response to Azospirillum spp. to the soil high N availability prior sowing.…”
Section: Resultsmentioning
confidence: 96%
“…(2017) reported that inoculation with A. brasilense in its liquid form via seed treatment, leaf application, or sowing furrow provided increases in wheat yield compared to the control treatment. On the other hand, Ferreira et al (2017) observed increases in wheat yield when inoculated with A. brasilense via seed and postemergence. However, the authors did not find significant increases when the inoculation was performed via leaf spraying.…”
Section: Table 1 Summary Of the Joint Analysis Of Variance And Coeffimentioning
confidence: 92%